Profil Kemampuan Berpikir Kreatif Peserta Didik Untuk Pembelajaran Fisika Terintegrasi Environmental Learning Pada Materi Perubahan Iklim (Universitas Negeri Surabaya, 2023)
Creative thinking skills have a tendency to be able to train students to come up with ideas and express themselves in the learning process. This research aims to determine the profile of creative thinking skills for integrated physics learning environmental learning on the subject of climate change involving 99 students in Jombang Regency. This research uses quantitative methods in analyzing the profile of students' creative thinking. The results of the analysis of creative thinking skills on climate change material for students in Jombang Regency, obtained the average of each creative thinking indicator, which is 21.75% so that students' creative thinking abilities at SMAN in Jombang Regency are categorized as not creative. it can be concluded that the ability of students on the creative thinking index related to climate change is categorized as not creative, and an integrated physics learning environment related to climate change is needed in the hope that students have a more meaningful physics learning experience because they directly interact with the surrounding environment.